2016
DOI: 10.1016/j.jbior.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression and function of inositol 1,4,5-trisphosphate 3-kinase C (ITPKC) in wild type and knock-out mice

Abstract: a b s t r a c tInositol 1,4,5-trisphosphate 3-kinase C (ITPKC) is the last identified member of the inositol 1,4,5-trisphosphate 3-kinases family which phosphorylates inositol 1,4,5-trisphosphate into inositol 1,3,4,5-tetrakisphosphate. Although expression and function of the two other family members ITPKA and ITPKB are rather well characterized, similar information is lacking for ITPKC. Here, we first defined the expression of Itpkc mRNA and protein in mouse tissues and cells using in situ hybridization and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…ITPKA knock-out mice exhibit increased synaptic plasticity and slight impairments of learning and memory [17,18], while deletion of ITPKB resulted in impaired stem cell homeostasis of immune cells [19]. ITPKC knock-out mice do not show an obvious altered phenotype [20] but a clinical relevant mutation of ITPKC is described in Kawasaki disease [21]. It is suggested that in T-cells ITPKC is a negative regulator, therefore Kawasaki disease-associated down-regulation of ITPKC results in over activation of T-cells [22].…”
Section: Discovery and Catalytic Role Of Itpksmentioning
confidence: 99%
“…ITPKA knock-out mice exhibit increased synaptic plasticity and slight impairments of learning and memory [17,18], while deletion of ITPKB resulted in impaired stem cell homeostasis of immune cells [19]. ITPKC knock-out mice do not show an obvious altered phenotype [20] but a clinical relevant mutation of ITPKC is described in Kawasaki disease [21]. It is suggested that in T-cells ITPKC is a negative regulator, therefore Kawasaki disease-associated down-regulation of ITPKC results in over activation of T-cells [22].…”
Section: Discovery and Catalytic Role Of Itpksmentioning
confidence: 99%
“…As KRAS has been frequently observed to be mutated in pancreatic cancer, attempts have been developed to generate effective RAS inhibitors as well as additional signaling molecules in this pathway. Attempts to inhibit the RAS/PI3K/PTEN/Akt/mTORC1/GSK-3 and other signaling pathways have been a central focus in many basic science laboratories and pharmaceutical companies for over three decades due to the involvement oncogenes in this pathway in human cancers (Yang et al, 2013;Fitzgerald et al, 2015;McCubrey et al, 2015;Anderson et al, 2016;Banfic et al, 2016;Cocco et al, 2016;Erneux et al, 2016;Falasca and Ferro, 2016;Fields et al, 2016;Geck and Toker, 2016;Maczis et al, 2016;Perdios et al, 2016;Pyne et al, 2016;Scarlata et al, 2016;Scoumanne et al, 2016;Tanaka et al, 2016;Ando et al, 2017;Carman and Han, 2017;Fujisawa, 2017;Geffken and Spiegel, 2017;Guo et al, 2017;Jang et al, 2017;Leonard and Johnson, 2017;Liu et al, 2017;Matsuzawa, 2017;McCubrey et al, 2017aMcCubrey et al, , 2017bMcCubrey et al, , 2017cMcCubrey et al, , 2017dObsil and Obsilova, 2017;Okazaki, 2017;Pyne et al, 2017;Ramos et al, 2017;Ratti et al, 2017;Rebello et al, 2017;Roth and Frohman, 2017;Rusnak and Fu, 2017;…”
Section: Introductionmentioning
confidence: 99%
“…Plotted results are mean (SD) for nCounter expression (n ϭ 45). Short description of genes not described in paper: ITPKB is expressed in cells with a brush border (104) but is also important in immune cells (92) and neurons (110). Its molecular function is related to intracellular calcium regulation (113).…”
Section: Evidence For Neurally Mediatedmentioning
confidence: 99%